Curriculum Theories and Their Politics in Ghana’s Pretetiary Education System - Mohammed, Atar Alphaa (Journal of Digital Learning and Education, 2023)
Ghana’s educational reforms are mostly influenced or initiated by politicians. The concept of politics is a means to an end and not an end in itself. This is experienced as a result of the cascading effect of the power of the macro level of curriculum theory to its micro level. These results are a direct reflection of Ghana's political and governmental structure. In most cases, a program's curriculum becomes less adaptable the more it is portrayed as an official document outlining the results and demands that must be accomplished. The under-listed topics, however, form part of the politics of curriculum theory in Ghana’s pre-tertiary educational system. A typical example is the duration of senior high school education. This paper provided enough evidence to espouse the role of politics in curriculum theory with a focus on the narrow and broad conception of politics. Similarly, it brings to bear the consequences of political power if left and checked coupled with some recommendations. The study uses a conceptual methodology aimed at developing and applying the politics of curriculum theory to the pre-tertiary education system in Ghana.